2002
DOI: 10.1074/jbc.m205759200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity and Flexibility of Cystic Fibrosis Transmembrane Conductance Regulator Transmembrane Segments Participate in Membrane Localization of a Charged Residue

Abstract: Polytopic protein topology is established in the endoplasmic reticulum (ER) by sequence determinants encoded throughout the nascent polypeptide. Here we characterize 12 topogenic determinants in the cystic fibrosis transmembrane conductance regulator, and identify a novel mechanism by which a charged residue is positioned within the plane of the lipid bilayer. During cystic fibrosis transmembrane conductance regulator biogenesis, topology of the C-terminal transmembrane domain (TMs 7-12) is directed by alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…different biogenesis pathways (19,20). Thus, despite their conserved topology, corresponding TM segments within the N-and C-terminal TMDs encode dissimilar topogenic information and use different translocation mechanisms to acquire their final topology (19,20). A recent publication showed that co-and post-translational steps as well as interactions between domains are required for proper folding of CFTR (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…different biogenesis pathways (19,20). Thus, despite their conserved topology, corresponding TM segments within the N-and C-terminal TMDs encode dissimilar topogenic information and use different translocation mechanisms to acquire their final topology (19,20). A recent publication showed that co-and post-translational steps as well as interactions between domains are required for proper folding of CFTR (21).…”
Section: Discussionmentioning
confidence: 99%
“…The bar graphs represent the average values of experiments measured in duplicate. different biogenesis pathways (19,20). Thus, despite their conserved topology, corresponding TM segments within the N-and C-terminal TMDs encode dissimilar topogenic information and use different translocation mechanisms to acquire their final topology (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The problems with proper orientation of the glycosylated loop may involve TM8. TM8 of CFTR is unusual because it has poor stop translocation properties, and removal of a negatively charged residue in TM8 (Asp 924) altered the topology of the extracellular loop between TM segments 7 and 8 (Carveth et al, 2002). Asp924 normally forms a salt bridge with Arg347 in TM6 of TMD1 (Cotten and Welsh, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro translation systems are well suited for such analysis and have been used to define mechanisms of CFTR topogenesis (11,12,15), identify early CFTR chaperone interactions (50), and characterize CFTR degradation pathways (48,51). We previously showed that rabbit reticulocyte lysate (RRL) supplemented with ER-derived microsomal membranes faithfully reconstitutes CFTR synthesis, core glycosylation, and membrane integration (45,51).…”
Section: In Vitro Formation Of Cftr Complexes-identification Of Cellularmentioning
confidence: 99%
“…A poorly understood, but important aspect of CFTR biogenesis is how folding and assembly of different domains are coordinated by cellular machinery in different cellular compartments. Topology of membrane-spanning domains is established during synthesis as the ribosome and nascent chain target to the ER membrane and bind a large protein-conducting channel (translocon) composed of Sec61␣ and its associated proteins (11)(12)(13)(14). As translation proceeds, internal sequences within the nascent CFTR polypeptide interact with the ribosome and translocon where they initiate polypeptide translocation into the ER lumen, orient cytosolic loops, and direct transmembrane segment integration into the lipid bilayer (12,(15)(16)(17).…”
mentioning
confidence: 99%